MODULI SPACES AND VECTOR BUNDLES - STEVEN B BRADLOW, et al (NEW YORK CAMBRIDGE UNIVERSITY PRESS, 2009)
Vector bundles and their associated moduli spaces are of fundamental importance in algebraic geometry. This volume, authored by some of the subject's leading experts, covers foundational material as well as focusing on research topics currently at the forefront of the field.
Keywords: MODULI THEORY; VECTOR BUNDLES